Task-Based Language Teaching Criteria in Textbook for Senior High School in Indonesia - Yuli Astriani; Rahmadi Nirwanto; Zaitun Qamariah (Universitas Majalengka, 2023)
The current study focused on activities and tasks that concluded in an English textbook used in a senior high school in Indonesia based on the TBLT's criteria. This study analyzed the content of an English textbook for senior high school grade X. The subject of this study was an English textbook titled